THE EFFECT OF HAMBURGER STRATEGY TOWARDS THE STUDENTS WRITING DESCRIPTIVE TEXT AT ONE ISLAMIC SENIOR HIGH SCHOOL - Aidafani, Jihan Chairunnisa; Bansa, Yorina An'guna; Soma, Robi; Rosita, Ratih (Universitas Muhammadiyah Muara Bungo, 2024)
ABSTRACT This research deals with the influence of the hamburger strategy in writing descriptive text. The hamburger strategy is a writing organization strategy that visually outlines the key components of a paragraph. When writing using the hamburger strategy, students will learn to remember how to build paragraphs and the importance of each component. This study was conducted using an experimental quantitative method. The population of this study was grade 11 students of Madrasah Aliyah Nururrodhiyah Jambi City. The researcher took 40 students as a sample and they were divided into two groups using total sampling. The first group was class XI A as an experimental class taught by implementing the hamburger strategy, while the second group was class XI B as a control class taught using conventional methods. This test consists of two types, namely Pre-Test and Post-Test. Data were analyzed using the T-Test formula on SPSS version 25. The results of the Independent Samples and Paired t tests. The average results of the same group taught using the Hamburger Strategy got a score of 0.000 which can be seen from the hypothesis criteria if the results are less than 0.05, it means Ha is rejected. And the results of the independent sample t-test showed an average difference of 68.700 and significant 2-tailed ≤ 0.05 (0.000 ≤ 0.05). It can be concluded that there is no significant difference in influence on students' writing ability between students taught with the Hamburger Strategy and students taught with conventional techniques or from teachers of Madrasah Aliyah Nururrodhiyah Jambi City. Keywords: descriptive text, hamburger strategy, writing skill